(untitled) (Islas, 2025)
Introduction: This study focuses on analyzing the neo-Kantianism of José del Perojo y Figueras within the Hispanic-American philosophical context of the late 19th century. Its general objective is to argue the particularities of this philosopher’s neo-Kantianism. Methods: The methods of analysis and synthesis were employed to process information and establish relationships between elements. The inductive-deductive method contributed to generalizations, while the logical-historical method was used to understand laws and their evolution. Results: The neo-Kantianism of this author posits that a functional and structural change in knowledge does not have to be imposed solely from a genetic perspective. If it were, the diversity of values and ideologies could not be explained. The progressive acquisition and development of individuals’ cognitive capacities is not merely a unilateral determination but a global one. Conclusions: José del Perojo reconciled elements of knowledge and moral action according to the philosophy of science and anthropological universals in psychological processes. This approach eliminated the metaphysical predominance of Kantian doctrine.